The Self‐Administered Witness Interview Tool (SAW‐IT): Enhancing witness recall of workplace incidents. Issue 6 (24th May 2019) - MacLean, Carla L.; Gabbert, Fiona; Hope, Lorraine
Summary: Given the often crucial role of witness evidence in occupational health and safety investigation, statements should be obtained as soon as possible after an incident using best practice methods. The present research systematically tested the efficacy of a novel Self‐Administered Witness Interview Tool (SAW‐IT), an adapted version of the Self‐Administered Interview designed to elicit comprehensive information from witnesses to industrial events. The present study also examined the effect of schematic processing on witness recall. Results indicate that the SAW‐IT elicited significantly more correct details, as well as more precise information than a traditional incident report form. Contextual information about a worker's safety history biased the reports of participant witnesses, confirming that witnesses should be shielded from extraneous post‐event information prior to reporting. Importantly, these results demonstrate that the SAW‐IT can enhance the quality of witness reports.